Catalytic layer and preparation method thereof, membrane electrode and fuel cell
By forming an alternating active layer of pore-containing long chain imidazolimine ionic liquid and Nafion resin solution on the surface of the catalytic layer base, the problem of pore blockage of the catalytic layer is solved, the high hydrophobicity and good gas transmission capacity of the catalytic layer are achieved, and the fuel cell is improved performance and durability.
Patent Information
- Application Number
- CN202411360953.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-07
AI Technical Summary
The existing proton exchange membrane fuel cell catalytic layer is blocked due to the hydrophilic resin, which blocks the formation of three interfaces, resulting in reduced battery efficiency and durability.
An active layer is arranged alternately with a hydrophobic zone and a hydrophilic zone composed of a pore-containing long-chain imidazoleimine ionic liquid and a Nafion resin solution, and is coated on the surface of the catalytic layer substrate by a slot method to form an independent water and gas transport channel.
The hydrophobicity and gas transmission capacity of the catalytic layer are improved, and the output performance and durability of the fuel cell are enhanced.
Smart Images

Figure CN119400874A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of fuel cell technology, and in particular to a catalyst layer and a preparation method thereof, a membrane electrode and a fuel cell. Background Art
[0002] Proton exchange membrane fuel cell (PEMFC) is a widely used fuel cell with good prospects. When the proton exchange membrane fuel cell is working, the Nafion resin used as the raw material for preparing the membrane electrode is hydrophilic, which causes the pores in the catalyst layer to also show hydrophilicity. As the battery continues to work, the water produced by the catalyst layer will be adsorbed onto the surface of the hydrophilic catalyst to form a water film, which will cause the pores of the catalyst to be blocked, blocking the formation of the three interfaces, and causing the efficiency of the battery to be greatly reduced. At the same time, long-term water accumulation in the membrane electrode will also have a great impact on the durability of the battery.
[0003] Polytetrafluoroethylene (PTFE) and fluorinated ethylene propylene (FEP) hydrophobic polymers are doped in the catalyst layer (CL) to improve the hydrophobicity of the catalyst layer; PTFE is often used to modify the catalyst layer to perform hydrophobic treatment of Pt nanoparticles, however, due to the lack of proton conductivity, this method is gradually eliminated. At present, the catalyst layer is prepared by mixing ionic liquids with resins, which helps to discharge water under high electric density. However, directly mixing ionic liquids with resins will cause uneven distribution of the two on the surface of the catalyst layer due to their poor compatibility, thereby limiting the hydrophobicity of the catalyst layer and seriously affecting the gas transmission capacity of the catalyst layer, and ultimately affecting the output performance of the fuel cell. Summary of the invention
[0004] The present application provides a catalyst layer and a preparation method thereof, a membrane electrode and a fuel cell to solve the following technical problem: how to improve the hydrophobicity of the catalyst layer.
[0005] In a first aspect, the present application provides a catalytic layer, the catalytic layer comprising a catalytic layer substrate and an active layer attached to at least a portion of the surface of the catalytic layer substrate, the active layer comprising a hydrophilic region and a hydrophobic region, the hydrophilic region and the hydrophobic region being alternately arranged in layers; wherein:
[0006] The raw material components of the hydrophobic region include pore-containing long-chain imidazole imide ionic liquid.
[0007] Optionally, the long-chain imidazole imide ionic liquid includes at least one of the following: 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide and 1-octyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide.
[0008] Optionally, the pore-containing long-chain imidazolidinium ionic liquid is obtained by forming pores in the long-chain imidazolidinium ionic liquid with a pore-forming agent.
[0009] Optionally, the pore-forming agent includes at least one of the following: ammonium bicarbonate, ammonium chloride, calcium carbonate, and polyvinyl alcohol.
[0010] Optionally, the pore-making process parameters include: a temperature of 10° C. to 15° C. and a time of 0.5 h to 1.5 h; and / or,
[0011] The weight ratio of the long-chain imidazole imide ionic liquid to the pore-forming agent is (9-11):1.
[0012] Optionally, the hydrophobic region further includes a first Nafion resin solution, and the solid content of the first Nafion resin solution is 1% to 2%.
[0013] Optionally, the weight ratio of the pore-containing long-chain imidazole imide ionic liquid to the first Nafion resin solution is 1:(8-10).
[0014] In a second aspect, the present application provides a method for preparing the catalytic layer according to any one of the embodiments of the first aspect, the method comprising:
[0015] A catalytic layer substrate and a porous long-chain imidazole imide ionic liquid are obtained;
[0016] Mixing the pore-containing long-chain imidazole imide ionic liquid, the first Nafion resin solution and a solvent to obtain a mixed solution;
[0017] The mixed solution and the second Nafion resin solution are respectively coated on at least a portion of the surface of the catalyst layer substrate by the intercalation method to form an activation layer containing a hydrophilic region and a hydrophobic region on the surface of the catalyst layer substrate to obtain a catalyst layer.
[0018] In a third aspect, the present application provides a membrane electrode, which comprises the catalytic layer described in any one embodiment of the first aspect.
[0019] In a fourth aspect, the present application provides a fuel cell, comprising the membrane electrode as described in any one embodiment of the third aspect.
[0020] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0021] The catalytic layer provided in the embodiment of the present application comprises a catalytic layer substrate and an active layer attached to at least part of the surface of the catalytic layer substrate, wherein the active layer comprises a hydrophilic region and a hydrophobic region, wherein the hydrophilic region and the hydrophobic region are alternately arranged in layers; wherein the raw material component of the hydrophobic region comprises a porous long-chain imidazolidinium ionic liquid. The long-chain imidazolidinium ionic liquid has excellent proton conductivity and hydrophobicity, which can improve the hydrophobicity of the catalytic layer while allowing the catalytic layer to take into account high proton conductivity; the hydrophobic region and the hydrophilic region of the porous long-chain imidazolidinium ionic liquid are alternately attached to the surface of the active layer, and the hydrophilic region has the function of conducting protons and reaction gases. Under the action of a certain gas pressure, the water generated by the catalytic layer will be preferentially discharged from the porous hydrophobic region, and the reaction gas will enter from the hydrophilic region next to it, thereby achieving the purpose of surface ordering of the catalytic layer with independent transmission channels for water and gas, thereby achieving the improvement of the hydrophobicity of the catalytic layer while taking into account good gas transmission capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0023] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0024] Figure 1 A schematic diagram of coating a hydrophilic region and a hydrophobic region of a catalytic layer provided in an embodiment of the present application;
[0025] Figure 2 A schematic diagram of a process for preparing a catalytic layer provided in an embodiment of the present application;
[0026] Figure 3 A microstructure diagram of a long-chain imidazolidinium ionic liquid provided in Example 1 of the present application;
[0027] Figure 4 A microstructure diagram of a porous long-chain imidazolidinium ionic liquid provided in Example 1 of the present application;
[0028] Figure 5 The voltage-current curve diagram of the membrane electrode obtained in Example 1 and Comparative Examples 1 to 5 of the present application used for single cell testing. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0030] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0031] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of singular or plural items. For example, "at least one of a, b, or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc or abc, where a, b, c can be single or plural, respectively.
[0032] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0033] In a first aspect, the present application provides a catalytic layer, the catalytic layer comprising a catalytic layer substrate and an active layer attached to at least a portion of the surface of the catalytic layer substrate, the active layer comprising a hydrophilic region and a hydrophobic region, the hydrophilic region and the hydrophobic region being alternately arranged in layers; wherein:
[0034] The raw material components of the hydrophobic region include pore-containing long-chain imidazole imide ionic liquid.
[0035] In the embodiment of the present application, the long-chain imidazolidinium ionic liquid has excellent proton conductivity and hydrophobicity, which can improve the hydrophobicity of the catalyst layer while allowing the catalyst layer to take into account high proton conductivity; the hydrophobic region and the hydrophilic region of the porous long-chain imidazolidinium ionic liquid are alternately attached to the surface of the active layer, and the hydrophilic region has the function of conducting protons and reaction gases. Under the action of a certain gas pressure, the water produced by the catalyst layer will be preferentially discharged from the porous hydrophobic region, and the reaction gas will be transmitted from the adjacent hydrophilic region to the surface of the Pt particles to react, thereby achieving the purpose of surface ordering of the catalyst layer with independent transmission channels for water and gas, thereby achieving the improvement of the hydrophobicity of the catalyst layer while the catalyst layer also takes into account good gas transmission capacity. Exemplarily, the hydrophilic region and the hydrophobic region are alternately attached to the surface of the active layer, and the active area of the catalyst layer substrate is 5cm*5cm. The hydrophobic region and the hydrophilic region are evenly distributed to achieve the ordering of the hydrophilic and hydrophobic regions on the surface of the catalyst layer substrate. Other ways to divide the active area equally are also acceptable. Figure 1 For a schematic diagram of coating the hydrophilic region and the hydrophobic region of a catalytic layer provided in an embodiment of the present application, see Figure 1 .
[0036] In some embodiments, the long-chain imidazolidinium ionic liquid includes at least one of the following: 1-butyl-3-methylimidazolium bistrifluoromethanesulfonyl imide and 1-octyl-3-methylimidazolium bistrifluoromethanesulfonyl imide.
[0037] In the embodiment of the present application, the long-chain imidazole imide ionic liquid can be a combination of one or more of 1-butyl-3-methylimidazolium bistrifluoromethanesulfonyl imide and 1-octyl-3-methylimidazolium bistrifluoromethanesulfonyl imide. These pore-forming agents are easily decomposed or volatilized at high temperatures and can be removed, so as to achieve a pore-forming effect. Since the proton conductivity is directly related to the chain length of the ionic liquid, the chain length of the theoretical ionic liquid is positively correlated with the proton conductivity. However, since the longer the chain, the more difficult it is to prepare the organic matter, the long-chain imidazole imide ionic liquid will be unstable in structure to a certain extent, and it is easy to decompose in the subsequent application in the preparation of membrane electrodes, and the proton conductivity enhancement effect of the long-chain imidazole imide ionic liquid is gradually weakened. Therefore, further, 1-butyl-3-methylimidazolium bistrifluoromethanesulfonyl imide with good stability and good proton conductivity is selected, and it is suitable for commercial applications.
[0038] In some embodiments, the pore-containing long-chain imidazolidinium ionic liquid is obtained by forming pores in the long-chain imidazolidinium ionic liquid with a pore-forming agent.
[0039] In some embodiments, the pore former includes at least one of the following: ammonium bicarbonate (NH4HCO3), ammonium chloride, calcium carbonate, polyvinyl alcohol.
[0040] In the embodiments of the present application, the pore-forming agent may be one or more combinations of ammonium bicarbonate, ammonium chloride, calcium carbonate, and polyvinyl alcohol; further, the products of NH4HCO3 during hot-pressing transfer are only NH3 and CO2, and the pore size that can be created is at the micron level, so ammonium bicarbonate (NH4HCO3) may be preferred.
[0041] In some embodiments, the pore-forming process parameters include: a temperature of 10° C. to 15° C., a time of 0.5 h to 1.5 h; and / or,
[0042] The weight ratio of the long-chain imidazole imide ionic liquid to the pore-forming agent is (9-11):1.
[0043] In the embodiment of the present application, the pore-containing long-chain imidazole imide ionic liquid can be obtained by forming pores in the long-chain imidazole imide ionic liquid with a pore-forming agent, and the pore-forming temperature can be 10°C to 15°C, and the time can be 0.5h to 1.5h, which can achieve the effect of fully forming pores in the long-chain imidazole imide ionic liquid and avoid decomposition of the pore-forming agent at low temperatures. Exemplarily, the pore-forming temperature can be 10°C, 11°C, 12°C, 13°C, 14°C, 15°C, etc., and the time can be 0.5h, 0.7h, 0.9h, 1.1h, 1.3h, 1.5h, etc. The weight ratio of the long-chain imidazole imide ionic liquid to the pore-forming agent can be (9 to 11): 1, which can effectively form a certain number and size of pores. If the weight ratio of the long-chain imidazole imide ionic liquid to the pore-forming agent is too large, the pore-forming effect may not be obvious, and the hydrophobicity of the subsequent catalytic layer may not be greatly improved; if the weight ratio of the long-chain imidazole imide ionic liquid to the pore-forming agent is too small, the structure of the ionic liquid may be destroyed, thereby rendering the hydrophobicity of the ionic liquid ineffective. For example, the weight ratio of the long-chain imidazole imide ionic liquid to the pore-forming agent may be 9:1, 10:1, 11:1, etc.
[0044] In some embodiments, the hydrophobic region further includes a first Nafion resin solution, and the solid content of the first Nafion resin solution is 1% to 2%.
[0045] In the embodiment of the present application, the hydrophobic region also includes a first Nafion resin solution, which can act as an adhesive. Since the long-chain imidazole imide ionic liquid has a strong fluidity, in order to enhance the adhesion of the long-chain imidazole imide ionic liquid to the catalyst layer substrate, the raw material components of the hydrophobic region include a porous long-chain imidazole imide ionic liquid and a first Nafion resin solution. The solid content of the first Nafion resin solution can be 1% to 2%, which can ensure the molding performance of the first Nafion resin solution coated on the catalyst layer substrate. Exemplarily, the solid content of the above-mentioned Nafion resin solution can be 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, etc.
[0046] In some embodiments, the weight ratio of the pore-containing long-chain imidazole imide ionic liquid to the first Nafion resin solution is 1:(8-10).
[0047] In the embodiment of the present application, the weight ratio of the porous long-chain imidazole imide ionic liquid to the first Nafion resin solution can be 1: (8-10), so that the porous long-chain imidazole imide ionic liquid and the first Nafion resin solution are fully mixed and uniform, ensuring the hydrophobicity of the porous long-chain imidazole imide ionic liquid, and improving the adhesion of the ionic liquid to the surface of the catalyst layer substrate, thereby ensuring the gas transmission capacity of the catalyst layer. Exemplarily, the weight ratio of the above-mentioned porous long-chain imidazole imide ionic liquid to the first Nafion resin solution can be 1: 8, 1: 9, 1: 10, etc.
[0048] In a second aspect, based on a general inventive concept, the present application provides a method for preparing a catalytic layer as described in any one of the embodiments of the first aspect, Figure 2 A schematic diagram of a process for preparing a catalytic layer provided in an embodiment of the present application; see Figure 2 , the method comprising:
[0049] S1, obtaining a catalyst layer substrate and a porous long-chain imidazole imide ionic liquid;
[0050] S2, mixing the pore-containing long-chain imidazole imide ionic liquid, the first Nafion resin solution and a solvent to obtain a mixed solution;
[0051] S3. Using the intercalation method, the mixed solution and the second Nafion resin solution are respectively coated on at least a portion of the surface of the catalyst layer substrate to form an activation layer containing a hydrophilic region and a hydrophobic region on the surface of the catalyst layer substrate to obtain a catalyst layer.
[0052] In the embodiment of the present application, the raw material components of the above-mentioned hydrophilic area include a second Nafion resin solution, and the hydrophilic area functions to conduct protons and gases; Nafion exhibits weak hydrophilicity, and water will gather on the surface of the Nafion resin. Under the action of gas pressure, the water will be squeezed out. If there is a hydrophobic area with large pores nearby, since Nafion is relatively dense, the water will be squeezed out from the large pores of the hydrophobic area under gas pressure; therefore, the hydrophilic area and the hydrophobic area form independent water and gas transmission channels, which are conducive to gas conduction and water discharge.
[0053] The solid content of the first Nafion resin solution and the second Nafion resin solution can be 1% to 2%. Under the action of the solvent, the ionic liquid and the first Nafion resin can be fully dissolved to avoid the uneven mixed solution due to the incompatibility of the two and the impact on the performance of the subsequent catalyst layer. The solvent can be an alcohol organic solvent. Since the porous long-chain imidazole imide ionic liquid is relatively dense, it may cause an increase in oxygen transmission resistance. The embodiment of the present application adopts an electrostatic spraying method to apply Nafion and ionic liquid slots on the surface of the catalyst layer to form a membrane electrode with an ordered hydrophobic structure on the cathode surface. Since macropores are made on the surface of the ionic liquid, water can be discharged only from the macropores in the hydrophobic ionic liquid area, and air can enter only from the Nafion area, forming a water-gas transmission cycle.
[0054] The preparation method of the catalytic layer is implemented based on the above-mentioned membrane electrode. The specific structure of the catalytic layer can refer to the above-mentioned embodiment. Since the preparation method of the catalytic layer adopts part or all of the technical solutions of the above-mentioned embodiments, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be repeated here one by one.
[0055] In a third aspect, based on a general inventive concept, the present application provides a membrane electrode, wherein the membrane electrode comprises the catalytic layer described in any one of the embodiments of the first aspect.
[0056] In the embodiment of the present application, the membrane electrode comprises the above-mentioned catalytic layer, and therefore, the membrane electrode has good water management capability.
[0057] The membrane electrode is realized based on the above-mentioned catalytic layer. The specific structure of the catalytic layer can refer to the above-mentioned embodiment. Since the membrane electrode adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.
[0058] In a fourth aspect, based on a general inventive concept, the present application provides a fuel cell, wherein the fuel cell comprises the membrane electrode as described in any one embodiment of the third aspect.
[0059] The embodiment of the present application prepares the catalyst layer by mixing ionic liquid with Nafion resin, which helps to discharge water under high electric density. The Nafion resin and the mixture of Nafion resin and ionic liquid are sprayed on the surface of the catalyst layer by slot spraying technology, forming orderly and independent gas, water and charge transmission channels, and the water removal channel is opened by pore making technology to more effectively discharge water in time. This coating method avoids the defect of uneven distribution of the ionic liquid and Nafion resin on the surface of the catalyst layer due to the poor compatibility of the two after mixing, thereby improving the gas transmission capacity of the catalyst layer, so that the membrane electrode containing the catalyst layer has good water management ability, thereby improving the output performance and durability of the fuel cell.
[0060] The fuel cell is realized based on the above-mentioned membrane electrode. The specific structure of the membrane electrode can refer to the above-mentioned embodiments. Since the fuel cell adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.
[0061] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0062] Example 1
[0063] A catalytic layer comprises a catalytic layer substrate and an active layer attached to at least a portion of the surface of the catalytic layer substrate, wherein the active layer comprises a hydrophilic region and a hydrophobic region, and the hydrophilic region and the hydrophobic region are alternately arranged in layers; wherein the raw material components of the hydrophobic region comprise a porous long-chain imidazole imide ionic liquid and a first Nafion resin solution, wherein the long-chain imidazole imide ionic liquid is 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide, and the solid content of the first Nafion resin solution is 1%; and the raw material components of the hydrophilic region comprise a second Nafion resin solution with a solid content of 1%.
[0064] The porous long-chain imidazole imide ionic liquid is obtained by forming pores in the long-chain imidazole imide ionic liquid with a pore-forming agent, specifically: the porous 1-butyl-3-methylimidazolium bistrifluoromethanesulfonyl imide is obtained by forming pores in the long-chain imidazole imide ionic liquid with a pore-forming agent NH4HCO3. The preparation method of the porous 1-butyl-3-methylimidazolium bistrifluoromethanesulfonyl imide comprises:
[0065] (1) Synthesis of 1-butyl-3-methylimidazolium bromide
[0066] First, 1-butyl-3-methylimidazolium bromide was synthesized. 3g of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and 5g of 1-bromobutane were added dropwise to 20ml of 20% acetonitrile solution, and then ultrasonicated in a water bath at low temperature (about 5°C) for 2 hours. The sample was then placed in an oven at 60°C to dry. After the solvent was completely evaporated, 1-butyl-3-methylimidazolium bromide solid was obtained. Please refer to the following reaction formula (1):
[0067]
[0068] (2) Synthesis of 1-butyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide
[0069] Take 1g of lithium ammonium bis(trifluoromethanesulfonyl imide) solution and 1g of 1-butyl-3-methylimidazolium bromide solid respectively, titrate the lithium ammonium bis(trifluoromethanesulfonyl imide) solution into the 1-butyl-3-methylimidazolium bromide solid obtained in step 1, and add 20ml of deionized water, and then put it in an ice-water bath for ultrasonic treatment for 1h, and then stand in the ice-water bath for 1h. Then, take the liquid below the water phase, which is the long-chain imidazolyl ionic liquid - 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl imide). Please refer to the following reaction formula (2):
[0070]
[0071] (3) Pore formation treatment with 1-butyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide
[0072] Take 0.1g NH4HCO3 solid and put it in a beaker. Slowly add the 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide liquid obtained in step 2 into the beaker. Control the weight ratio of ionic liquid to NH4HCO3 solid to be 10:1. Then gradually add 10ml of water and isopropanol solution with a volume ratio of 1:1, and stir in an ice water bath at 10°C for 1h. At this time, NH4HCO3 will be dissolved in the imidazolyl ionic liquid to obtain a porous 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ionic liquid.
[0073] A membrane electrode comprises the catalyst layer in Example 1, and a method for preparing the membrane electrode comprises:
[0074] 1 g of Pt / C catalyst (Umicore, Pt0690) was mixed with 6 g of water, 4 g of isopropanol, and 5% solid content Nafion resin, and dispersed by high-speed shearing for 1 h. After the dispersion was completed, the slurry was degassed, and then coated on a flat PTFE base membrane, placed in an oven at 80°C for 10 min, and cut into an active area of 5 cm*5 cm to obtain a cathode catalyst layer substrate; the cathode catalyst layer substrate was hot-pressed together with a proton membrane (Gore) and an anode, and sandwiched with a gas diffusion layer to obtain CCM-1;
[0075] 8 g of Nafion solution was diluted to a solid content of 1% with a solution of 16 g of water and 16 g of isopropanol in a mass ratio of 1:1 to obtain a first Nafion solution and a second Nafion solution; the second Nafion solution was coated on the surface of the cathode catalyst layer substrate of CCM-1 by ultrasonic spraying, the spraying path was linear spraying, and the spraying interval was 5 mm each time;
[0076] Take 0.1g of the porous 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ionic liquid and 0.8g of the first Nafion solution, add 10g of isopropanol while stirring in a 30°C water bath, and then apply the slurry to the surface of the cathode catalyst layer by ultrasonic spraying (see Figure 1 As shown), a cathode catalyst layer CCM-1 with ordered hydrophobic surface was obtained, which was then dried in an oven at 80°C for 10 min and naturally dried before being sandwiched with a gas diffusion layer to obtain sample No. 1 (MEA-1).
[0077] Comparative Example 1
[0078] Preparation of membrane electrode by transfer method: 1 g of Pt / C catalyst (Umicore, Pt0690) was mixed with 6 g of water, 4 g of isopropanol, 8 g of 5% Nafion resin and 1 g of porous 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide ionic liquid, and dispersed by high-speed shear for 1 hour. After degassing, the slurry was coated on a flat PTFE base membrane, placed in an oven at 80°C for drying for 10 minutes, and then cut into an active area of 5 cm*5 cm to obtain a cathode catalyst layer; the cathode catalyst layer was hot-pressed together with the proton membrane (Gore) and the anode (CCM-2), and sandwiched with the gas diffusion layer to obtain sample No. 2 (MEA-2).
[0079] Comparative Example 2
[0080] The membrane electrode was prepared by spraying the ionic liquid on the CCCL side: 1 g of Pt / C catalyst (Umicore, Pt0690) was mixed with 6 g of water, 4 g of isopropanol, and 8 g of 5% Nafion resin, and then dispersed by high-speed shear for 1 h to obtain the first slurry; 0.8 g of Nafion resin solution with a solid content of 1%, 7.8 g of water, 5.2 g of isopropanol, and 0.1 g of porous 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide ionic liquid were mixed by super shear. After acoustic stirring for 1 hour, the second slurry was obtained; the first slurry was coated on a flat PTFE base membrane, placed in an oven at 80°C for drying for 10 minutes, cut into an active area of 5cm*5cm, and hot-pressed together with a proton membrane (Gore) and an anode to obtain CCM-3; the second slurry was coated on the surface of the cathode catalyst layer of CCM-3 by ultrasonic spraying, and then dried in an oven at 80°C for 10 minutes, and then naturally dried and sandwiched together with the gas diffusion layer to obtain sample No. 3 (MEA-3).
[0081] Comparative Example 3
[0082] Membrane electrode: 1 g of Pt / C catalyst (Umicore, Pt0690) is mixed with 6 g of water, 4 g of isopropanol and 8 g of 5% Nafion resin, and dispersed by high-speed shear for 1 hour to obtain a first slurry; the first slurry is coated on a flat PTFE base membrane, placed in an oven at 80°C for drying for 10 minutes, cut into an active area of 5 cm*5 cm, and hot-pressed together with a proton membrane (Gore) and an anode to obtain CCM-4. The cathode catalyst layer CCM-4 is sandwiched with a gas diffusion layer to obtain sample No. 4 (MEA-4).
[0083] Comparative Example 4
[0084] On the basis of the disclosure of Comparative Example 2, the difference between the technical solutions of Comparative Example 4 and Comparative Example 2 is that the 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide ionic liquid is not subjected to pore-forming treatment, and finally sample No. 5 (MEA-5) is obtained.
[0085] Comparative Example 5
[0086] The difference between the technical solutions of Example 5 and Example 1 based on the disclosure of Example 1 is that the 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide ionic liquid is not subjected to pore-forming treatment, and finally sample No. 6 (MEA-6) is obtained.
[0087] Figure 3 A microstructure diagram of a long-chain imidazolidinium ionic liquid provided in Example 1 of the present application; Figure 4 This is a microstructure diagram of a porous long-chain imidazolidinium ionic liquid provided in Example 1 of the present application; see Figure 3-4, and refer to the pore size change results before and after pore formation by long-chain imidazolidinium ionic liquid as shown in Table 1 below.
[0088] Table 1 The results of pore size changes before and after pore formation by long-chain imidazolidinium ionic liquid
[0089] Ionic Liquids Maximum pore size / nm Maximum pore size / nm Average pore size / nm Hole width / μm After puncture 20.11 10.21 15.03 2-5 Before puncture 1200.3 607.8 902.6 <10
[0090] From Table 1 and Figure 3-4 It can be seen that NH4HCO3 successfully creates pores in 1-butyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide ionic liquid.
[0091] The membrane electrodes obtained in Example 1 and Comparative Examples 1 to 5 were respectively used to be assembled into a single cell fixture for single cell testing. The specific steps include: assembling the prepared membrane electrode in a single cell fixture, controlling the compression rate to 10-30%, and placing it in a single cell test bench (Qun Yi 890e) for testing, wherein hydrogen is supplied to the anode side and air is supplied to the cathode side, and the gases at the anode and cathode react with excess fuel, and the excess coefficients are 1.5-2 for the anode and 1.5-4 for the cathode, respectively. Before the performance test, the battery needs to be activated for 4-10 hours, and the activation method is adopted under constant load mode under high current density, and the activation voltage is 0.3V-0.6V.
[0092] Figure 5 This is a voltage-current curve diagram of the membrane electrode obtained in Example 1 and Comparative Examples 1 to 5 of the present application for single cell testing; please refer to Figure 5 , indicating that the performance of the membrane electrode of Example 1 (MEA-1) is obviously the best at high current density, and in the mass transfer area (2000mA / cm 2 The above) have higher output performance, indicating that the membrane electrode prepared by slot spraying has better mass transfer effect, improves the gas transmission capacity of the catalyst layer, and thus improves the output performance of the fuel cell. Therefore, this also reflects that the catalyst layer provided in Example 1 has better water and gas transmission capacity;
[0093] In comparative example 1 (MEA-2), the porous ionic liquid and Nafion resin were mixed and then the membrane electrode was prepared by traditional transfer technology. As a result, it was found that the performance dropped rapidly. This may be because the poor compatibility between the resin and the ionic liquid resulted in uneven distribution of the mixed slurry on the surface of the catalyst layer, resulting in a decrease in the number of three-phase interfaces (the interface of the chemical reaction, which is the intersection of the three phases of reaction gas, charged ions (protons, electrons) and catalyst), slowing down the chemical reaction, and reducing the output performance. As a result, the gas transmission capacity of the catalyst layer is poor, which seriously affects the output performance of the battery; although comparative example 2 (MEA-3) avoids the degradation of battery performance due to direct mixing of Nafion and ionic liquid, the ionic liquid containing Nafion is sprayed on the catalyst layer in the form of spraying, and only a single area is set, but slot spraying is not used (the present application sets alternating hydrophilic and hydrophobic double areas). In comparative example 2, the ionic liquid is coated on the surface of the catalyst layer, resulting in an overly dense surface, which greatly increases the fuel The transmission pathway of the material (oxygen) affects the output performance of the battery, and the final output performance of the battery is lower than that of Example 1; Comparative Example 3 (MEA-4) is a standard sample (without using ionic liquid), and it can be found that the performance of the catalyst layer prepared by using ionic liquid and spraying method in the mass transfer zone is significantly higher than that of the traditional standard catalyst layer, which can prove that the hydrophobic catalyst layer can improve the water and gas management capabilities of the fuel cell; Comparative Example 4 (MEA-5) uses non-porous 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide as the ionic liquid, and uses the same comparative example 2 to prepare a membrane electrode, and the output performance of the battery is lower than that of Comparative Example 2; Comparative Example 5 (MEA-6) uses non-porous 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide as the ionic liquid, and uses the same exemplary example 1 to prepare a membrane electrode, and the output performance of the battery is lower than that of Example 1; Therefore, the analysis of Example 1, Comparative Example 4 and Comparative Example 5 proves the feasibility of pore-forming for ionic liquid to improve the output performance of the fuel cell.
[0094] One or more technical solutions in the embodiments of the present application also have at least the following technical effects or advantages:
[0095] (1) 1-butyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide has excellent proton conductivity and hydrophobicity as an ionic liquid. The embodiment of the present application uses NH4HCO3 to create macropores on the ionic liquid to form independent water transmission channels, and the synthesis method is simple. In the precursor ionic liquid coated with the catalytic layer, NH4HCO3 decomposes after being placed in an 80°C oven, leaving micron pores at the original position, and only volatile NH3 and CO2 are produced, which will not cause pollution to the sample;
[0096] (2) Since 1-butyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide is relatively dense, it may lead to an increase in oxygen transmission resistance. In the embodiment of the present application, Nafion and ionic liquid are coated on the surface of the catalyst layer by electrostatic spraying to form a membrane electrode with an ordered hydrophobic structure on the cathode surface. Since pores are formed on the surface of the ionic liquid, water can be discharged only from the large pores in the hydrophobic ionic liquid area, and air can enter only from the hydrophilic area of Nafion, forming a water-gas transmission cycle. After IV testing, it was found that MEA-1 has the best mass transfer at high current density and has the highest rated and maximum output power.
[0097] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A catalytic layer, characterized in that: The catalytic layer comprises a catalytic layer substrate and an active layer attached to at least a portion of the surface of the catalytic layer substrate, wherein the active layer comprises a hydrophilic region and a hydrophobic region, and the hydrophilic region and the hydrophobic region are alternately arranged in layers; wherein, The raw material components of the hydrophobic region include pore-containing long-chain imidazole imide ionic liquid.
2. The method according to claim 1, characterized in that The long-chain imidazole imide ionic liquid includes at least one of the following: 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl imide) and 1-octyl-3-methylimidazolium bis(trifluoromethanesulfonyl imide).
3. The method according to claim 1 or 2, characterized in that: The pore-containing long-chain imidazolidinium ionic liquid is obtained by forming pores in the long-chain imidazolidinium ionic liquid with a pore-forming agent.
4. The catalytic layer according to claim 3, characterized in that The pore-forming agent includes at least one of the following: ammonium bicarbonate, ammonium chloride, calcium carbonate, and polyvinyl alcohol.
5. The catalytic layer according to claim 3, characterized in that The process parameters of the pore making include: temperature of 10°C to 15°C, time of 0.5h to 1.5h; and / or, The weight ratio of the long-chain imidazole imide ionic liquid to the pore-forming agent is (9-11):
1.
6. The catalyst layer according to claim 1, characterized in that The hydrophobic region further comprises a first Nafion resin solution, and the solid content of the first Nafion resin solution is 1% to 2%.
7. The catalyst layer according to claim 6, characterized in that The weight ratio of the pore-containing long-chain imidazole imide ionic liquid to the first Nafion resin solution is 1:(8-10).
8. A method for preparing a catalyst layer according to any one of claims 1 to 7, characterized in that: The method comprises: A catalytic layer substrate and a porous long-chain imidazole imide ionic liquid are obtained; Mixing the pore-containing long-chain imidazole imide ionic liquid, the first Nafion resin solution and a solvent to obtain a mixed solution; The mixed solution and the second Nafion resin solution are respectively coated on at least a portion of the surface of the catalyst layer substrate by the intercalation method to form an activation layer containing a hydrophilic region and a hydrophobic region on the surface of the catalyst layer substrate to obtain a catalyst layer.
9. A membrane electrode, characterized in that: The membrane electrode comprises the catalyst layer according to any one of claims 1 to 7.
10. A fuel cell, characterized in that: The fuel cell comprises the membrane electrode according to claim 9.
Citation Information
Cited By
Preparation method of platinum alloy catalyst supported by three-dimensional hydrophobic structure
CN121484099A